DIFFERENT WAYS OF TEACHING ENGLISH WITH INTERACTIVE GAMES IN SECONDARY SCHOOLS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the effectiveness of using interactive games as a method for teaching English to students in secondary schools. Through interactive games, educators are capable of transforming a dull and a more traditional way of teaching into captivating learning sessions. This dissertation narrows down to the effects of interactive games for English purpoes in teaching secondary students with effective communication skills, language acquisition and classroom behavior. Interactive games have lots to offer for a language classroom. Most importantly, they serve to greatly enhance a learner's motivation. In the normal classroom, many students consider learning a language as a very boring and difficult task.